Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content: 1. Study, Investigation and Interpretation (The first four verses of Surat Al-Baqarah) Written by: Al-Fadil Al-Yamani in his Book (Pearl Shells in Al-Kashaf Intricacies’ Solution) Mr. Akram Mohammed Abdullah 2. The book of Al-Hisbah, the Abodes and What pertains to Imam as well as Other Issues Written by the Scholar and Judge: Abdullah bin Mohammed bin Abdullah bin Hamza bin Abi Najm (died in 647 A.H.) – A study and an investigation – Dr. Mohammed Yahya Ahmed Abdullah Al-Qadi 3. The verse of preserving money and not transgressing in Surat Al-Nisa: An analytical study Mr. Ahmed Mohamed Ahmed Al-Khawaldeh , Prof. Jihad Muhammad Faisal Al-Nuseirat 4. The Purposes of Islamic Sharia Which Related to the Mandatory Provision Mr. Abdullah Ahmed Ahmed Dahman 5. Study and Investigation: Interpretation Surat Ibrahim for Al-Fadhel Al-Yemeni in His Note Durar Al-Sadaf Fi Hal Oqad Al-Kashaf Dr. Omar Fuaini Omar Maqbol 6. The impact of the difference in the significance of the absolute command on obligation in the jurisprudential branches.(Analytical، descriptive study) Dr. Rahma Abdullah Musleh Al-Warraq 7. The method of scholar " Yaḥya Ibn-Aḥmad Ibn-Muẓaffar" in weighting and reasoning in his book "Al-Kawakib Al-Naiyira Al-kashifa li-Maanai Al-taḏkira" "Book of Al- Eibadat Enmudhajan" Dr. Fawakha Saleh Al-Gabri 8. The judge bin Shamlah Bahanan and his book Neil Al-Maqsoud in explanation of Sunan abi Daoud from the chapter of what came in answering the invitation to the chapter of the desirability of feast: (transcription and commenting) Dr. Sawsan Ali Bazarah